Challenges and opportunities of enhancing cold flow properties of biodiesel via heterogeneous catalysis. (1st June 2016) - Anwar, Adeel; Garforth, Arthur
Highlights: Lipid derived biofuel is primarily being investigated in two forms: renewable diesel and biodiesel. The long straight chain fatty acid molecular composition found in naturally occurring oils produces fuel of a lesser quality. Cold flow properties and oxidative stability are the two major concerns in terms of quality. Hydroprocessing using heterogeneous catalysis is considered to be the most innovative solution. Dewaxing (hydrocracking and hydroisomerisation) offers the most enticing prospects. Abstract: Concerns over climate change are necessitating the need for alternative greener fuel. Biodiesel is widely considered to be a key contributor to alleviating this concern. At present the biodiesel sector faces a number of challenges including technical challenges such as improving the quality of biodiesel to match that of crude oil derived diesel. One of the key challenges in the quality arena is improving the cold flow properties to enable wider geographic and seasonal operability. This review discusses in depth the various options which can be deployed to address this issue in an efficient and effective manner, with heterogeneous catalysis offering fascinating prospects.